2021
DOI: 10.1371/journal.pone.0252513
|View full text |Cite
|
Sign up to set email alerts
|

Integrating a problem-solving intervention with routine care to improve psychosocial functioning among mothers of children with sickle cell disease: A randomized controlled trial

Abstract: Objective To assess the feasibility of a problem-solving skills training intervention in improving psychological outcomes in mothers of infants with sickle cell disease (SCD). Design and methods This parallel randomized controlled trial recruited 64 babies with SCD, 6 to 12 months of age, and their mothers. Baseline measurements assessed mothers’ coping and problem-solving skills, depression, and parental stress before random assignment to intervention or control groups (n = 32 each). Problem-solving skills … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…After removal of duplicates ( n = 2,298), a total of 4,884 titles and abstracts were assessed for eligibility, 296 of which fulfilled the eligibility criteria. After inspection of full-texts, a total of 23 studies (Abhari et al, 2021; Asnani et al, 2021; Baumgartner et al, 2021; Chaharrahifard et al, 2021; Dayhimi et al, 2020; Gao et al, 2010, 2015; George et al, 2020; Guo et al, 2021; Koçak et al, 2021; Li et al, 2019; Mao et al, 2012; Ozcan & Eryilmaz, 2021; Özçoban et al, 2022; Rajeswari & SanjeevaReddy, 2020; Ramezani et al, 2017; Rong et al, 2021; Rotheram-Borus, Richter et al, 2014; Rotheram-Borus, Tomlinson et al, 2014; Sanfilippo et al, 2020; Sapkota et al, 2022; Tripathy et al, 2010; Vargas-Porras et al, 2021) from 28 publications (Supplemental Appendix D) with 24,442 participants were included in the systematic review. Of these, 22 provided data suitable for the meta-analysis (Figure 1 and Supplemental Appendix D, E).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After removal of duplicates ( n = 2,298), a total of 4,884 titles and abstracts were assessed for eligibility, 296 of which fulfilled the eligibility criteria. After inspection of full-texts, a total of 23 studies (Abhari et al, 2021; Asnani et al, 2021; Baumgartner et al, 2021; Chaharrahifard et al, 2021; Dayhimi et al, 2020; Gao et al, 2010, 2015; George et al, 2020; Guo et al, 2021; Koçak et al, 2021; Li et al, 2019; Mao et al, 2012; Ozcan & Eryilmaz, 2021; Özçoban et al, 2022; Rajeswari & SanjeevaReddy, 2020; Ramezani et al, 2017; Rong et al, 2021; Rotheram-Borus, Richter et al, 2014; Rotheram-Borus, Tomlinson et al, 2014; Sanfilippo et al, 2020; Sapkota et al, 2022; Tripathy et al, 2010; Vargas-Porras et al, 2021) from 28 publications (Supplemental Appendix D) with 24,442 participants were included in the systematic review. Of these, 22 provided data suitable for the meta-analysis (Figure 1 and Supplemental Appendix D, E).…”
Section: Resultsmentioning
confidence: 99%
“…Psychosocial interventions were provided by primary-level health care workers (e.g. midwives, nurses, obstetricians) in 16 studies (Abhari et al, 2021; Asnani et al, 2021; Chaharrahifard et al, 2021; Dayhimi et al, 2020; Gao et al, 2010, 2015; Guo et al, 2021; Koçak et al, 2021; Li et al, 2019; Mao et al, 2012; Ozcan & Eryilmaz, 2021; Özçoban et al, 2022; Rajeswari & SanjeevaReddy, 2020; Ramezani et al, 2017; Sapkota et al, 2022). Community workers (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 summarizes the characteristics of the included 23 RCTs published between 2002 and 2021. Most were conducted in the US (21 studies), with 1 study each in Australia and Jamaica . Twenty-one studies used a 2-arm RCT design.…”
Section: Resultsmentioning
confidence: 99%
“…Most were conducted in the US (21 studies), with 1 study each in Australia and Jamaica . Twenty-one studies used a 2-arm RCT design. In addition, most studies (12 [52%]) reported that a control group received usual care.…”
Section: Resultsmentioning
confidence: 99%